A look to the future in non‐alcoholic fatty liver disease: Are glucagon‐like peptide‐1 analogues or sodium‐glucose co‐transporter‐2 inhibitors the answer?. Issue 12 (6th October 2020) - Vincent, Rebecca K.; Williams, David M.; Evans, Marc
Abstract: The increasing prevalence of diabetes and non‐alcoholic fatty liver disease (NAFLD) is a growing public health concern associated with significant morbidity, mortality and economic cost, particularly in those who progress to cirrhosis. Medical treatment is frequently limited, with no specific licensed treatments currently available for people with NAFLD. Its association with diabetes raises the possibility of shared mechanisms of disease progression and treatment. With the ever‐growing interest in the non‐glycaemic effects of diabetes medications, studies and clinical trials have investigated hepatic outcomes associated with the use of drug classes used for people with type 2 diabetes (T2D), such as glucagon‐like peptide‐1 (GLP‐1) analogues or sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors. Studies exploring the use of GLP‐1 analogues or SGLT2 inhibitors in people with NAFLD have observed improved measures of hepatic inflammation, liver enzymes and radiological features over short periods. However, these studies tend to have variable study populations and inconsistent reported outcomes, limiting comparison between drugs and drug classes. As these drugs appear to improve biomarkers of NAFLD, clinicians should consider their use in patients with NAFLD and T2D. However, further evidence with greater participant numbers and longer trial durations is required to support specific licensing for people with NAFLD. Larger trials would allow reporting of major adverse hepatic events, akin to cardiovascular and renal outcome trials, to be determined. This would provide a more meaningful evaluation of the impact of these drugs in NAFLD. Nevertheless, these drugs represent a future potential therapeutic avenue in this difficult‐to‐treat population and may beget significant health and economic impacts.